AB0684 Bone Metabolism in a Large Cohort of Patients with Systemic Sclerosis. (9th June 2015) - Caimmi, C.; Caramaschi, P.; Barausse, G.; Orsolini, G.; Idolazzi, L.; Gatti, D.; Viapiana, O.; Rossini, M.; Adami, S.
Abstract : Background: Patients with systemic sclerosis (SSc) may have classical and disease-related risk factors for osteoporosis (OP)(1) but there is no agreement about the association between SSc and OP (2). Objectives: The aim of this study was to evaluate in a large size cohort of SSc patients bone mineral density (BMD) and to analyze its possible determinants. Methods: 106 consecutive outpatients affected by SSc were enrolled for the present study. All patients underwent evaluation of BMD and vertebral fractures (VFA) using DXA (GE Lunar iDXA), pulmonary function test, nailfold videocapillaroscopy, blood samples. For the statistical analysis we preferred to use Z-score to BMD or T-score since the population was composed by patients with different ages and of both sexes. Results: Most patients were female with a limited disease pattern (84, 9% and 651, % respectively). Mean age was 58.8±12.6, mean BMI was 25.3±4.4 and disease duration was 10 years ±5.8. 25.7 had interstitial lung disease. Parameters correlated with bone metabolism are shown in table 1 . 31.1% and 26.4% respectively were or had been smokers or steroid-treated. 65.1% were taking vitamin D supplementation and 18.9% bisphosphonates. 74.4% of women were in menopause. Mean neck Z-score was significantly lower than 0. No significant differences were found for other sites. Female patients were shown to have a total femur and neck Z-score significantly lower than 0 (p=0.028 and p<0.001, respectively). This data was not confirmed for other sites. Thirteen patients out of 96 with a good quality VFA (13.4%) had at least one morphometric non-clinical vertebral fracture. In univariate analysis total femur Z-score was lower in female (p=0.050) and in smokers (p=0.063) and positively correlates with BMI (p=0.001), neck Z-score positively correlates with age (p=0.016) and whole body Z-score positively correlates with BMI (p<0.001). No correlations were found for lumbar Z-score. The multivariate analysis confirmed the positive correlation between BMI and total femur and whole body Z-score and between age and neck femur Z-score (p=0.01, p<0.001 and p=0.019, respectively). Lung fibrosis was shown to correlate with a lower whole body Z-score in multivariate analysis (p=0.049). All data were confirmed even if corrected for vitamin D serum levels and vitamin D supplementation. Conclusions: Our study evaluates a large sized and well characterized SSc population by a quite complete multivariate analysis aiming to control the most important confounding factors for OP. We found a modest risk of low BMD in patients with SSc and the important protective role of BMI. References: Loucks J, Pope JE. Osteoporosis in scleroderma. Semin Arthritis Rheum 2005;34:678-82 Omair MA. Low Bone Density in Systemic Sclerosis. A Systematic Review. J Rheumatol 2013;40:1881-90. Disclosure of Interest: None declared